Executive dysfunction in high functioning autism - Burnett, Hollie (The University of Edinburgh, 2017)
Background: There is presently a lack of consistency in research designed to measure executive functioning (EF) in autism that may be attributable to lack of homogeneity or comorbid conditions (i.e. learning disability or additional diagnosis) in test samples. Aim: A systematic review focused on a subset of EF (verbal fluency: VF) was conducted, using only studies of high-functioning individuals with autism (HFA) without an additional diagnosis or learning disability. An empirical study was conducted comparing the executive functioning profile of individuals with HFA and typically developed (TD) individuals. Method: For the systematic review, 16 studies met the specified inclusion criteria, depicting 15 semantic (category), 14 phonological (letter), and 6 switching (categories) VF tasks. In order to assess potential bias, the available VF information of the included papers was scrutinised by the author and an independent clinical practitioner. For the empirical paper, 22 HFA and 22 TD participants (mean age = 28, range = 17-73, 52% male) without a comorbid condition, learning disability or brain injury completed three subtests from the WAIS-IV (vocabulary, block design and digit span) and all subtests of the Delis–Kaplan Executive Functioning System (D-KEFS). Results: For the systematic review, a minority of semantic and phonological VF studies reported a significant difference between typically developed and HFA populations. Five of the six semantic switching studies reported a significant difference between groups. All papers included were of good or adequate quality and inter-rater reliability was high. For the empirical paper, the HFA group performed significantly poorer on the switching condition of the design fluency task, semantic conditions of the verbal fluency task and on the word context task overall. No other significant differences were observed. Summary: Although the systematic review concluded that there was insufficient evidence to support that disfluency can be attributed to autistic symptomology, the empirical study found that the HFA group performed poorer than TD in semantic VF and other subtests designed to measure generating novel ‘imaginative’ ideas, without visual cues to aid performance. The deficit on these subtests was increased when there was the added condition requiring the participant to switch between newly formed concepts. Conclusions: Although in VF, results are mixed, the empirical study demonstrates that even in a group of high-functioning individuals there are still measurable differences in EF between TD and HFA samples that may not be apparent through more general cognitive testing. Implications for using a neuropsychological profile for adults with HFA are discussed.
Keywords: autism spectrum disorder; ASD; autism; executive functioning; Asperger